Silica-coated La0.75Sr0.25MnO3 nanoparticles for magnetically driven DNA isolation - Trachtová, Stěpánka; Kaman, Ondřej; Spanová, Alena; Veverka, Pavel; Pollert, Emil; Rittich, Bohuslav (Journal of separation science, 2011)
Magnetic La(0.75)Sr(0.25)MnO(3) nanoparticles possessing an approximately 20-nm-thick silica shell (LSMO(0.25)@SiO(2) ) were characterised and tested for the isolation of PCR-ready bacterial DNA. The results presented here show that the nanoparticles do not interfere in PCR. DNA was apparently reversibly adsorbed on their silica shell from the aqueous phase system (16% PEG 6000-2 M NaCl). The method proposed was used for DNA isolation from complex food samples (dairy products and probiotic food supplements). The isolated DNA was compatible with PCR. The main advantages of the nanoparticles tested for routine use were their high colloidal stability allowing a more precise dosage and therefore high reproducibility of DNA isolation.
Keywords: Magnetic Phenomena; Silicon Dioxide; oxidy; Lactobacillus; sloučeniny manganu; polymerázová řetězová reakce; Polymerase Chain Reaction; Strontium; DNA bakterií; Oxides; Nanoparticles; lanthan; DNA, Bacterial; nanočástice; magnetické jevy; Magnetics; oxid křemičitý; magnetismus; stroncium; Manganese Compounds; Lanthanum